Beyond growing crops: How community gardening shapes the residents’ meaning of participation - Shahida Mohd Sharif; Norsidah Ujang; Shureen Faris Abdul Shukor; Sreetheran Maruthaveeran (IOP Publishing Ltd, 2024)
Community gardening is situated against the backdrop of the 'Bumi Hijau' campaign, which aims to foster urban agriculture engagement in Malaysia. It emerges as a vital practice that promotes inclusivity, diversity, and empowerment within urban areas. This study explores the experiences of community gardening among residents of Seri Perlis 2, a public housing neighborhood in Kuala Lumpur. The study reveals diverse identity formation, empowerment, and knowledge acquisition among participants who span various ages, professions, and backgrounds, embodying the broader demographic spectrum of the community. The study employs qualitative semi-structured interviews to gather rich data, enabling an in-depth exploration of participants' experiences. It illustrates how community gardening participants shape their understanding of participation beyond mere crop cultivation. According to LB, his commitment to participation reflects a sense of accountability to government calls for food security and cost reduction. HC's transformation through his participation showcases identity reshaping. AK's active involvement has boosted cooperative income, while AM's participation has highlighted its educational aspect, providing access to vast agricultural knowledge from multiple sources. Data analysis and interpretation have uncovered themes that point to the capacity of community gardening participation to empower potential in identity formation and its role as a platform for continuous learning. The exploration of their experiences has encapsulated other themes like unity, agricultural heritage preservation, and empowerment, transcending crop cultivation as it redefines participants' engagement. These diverse experiences reinforce the transformative capacity of community gardening participation, aligning with previous research and government campaigns. Amid differing perspectives and experiences, the potential for personal growth and community cohesion through community gardening becomes evident, contributing to sustainable urban community development.